Some aspects of the flow near a swept attachment line with particular reference to boundary layer transition - Poll, D. I. A. (Cranfield University, 1978)
The general properties of the flow at infinite swept attachment line have been investigated theoretically and experimentally. By using the concepts of reference temperature and Reynolds analogy it has been possible to produce a simple, semi-empirical calculation technique for skin friction and heat transfer rate which is valid for free stream Mach numbers up to eight both with and without heat transfer to the body surface. A consideration of the predictions made by this method shows that an understanding of the transition phenomenon is particularly important and therefore the response of the incompressible attachment line boundary layer to two-dimensional trip wires and turbulent boundary layers generated on bounding end plates has been investigated experimentally. A sufficiently wide range of parameters has been covered to ensure that the results are typical of full scale flight situations and simple prediction criteria have been derived. By re-evaluating existing data from several different sources it has been possible to extend the validity of some of the principal results to include flight at hypersonic speeds. In addition to the mechanism of transition via cross instability has been studies experimentally for incompressible flow conditions and prediction criteria which are compatible with advanced boundary layer calculation methods, have been developed with the aid of liner stability theory and results obtained from the re-evaluation of several early experimental investigations. In all cases sample calculations and the practical implications of the various predictions have been discussed.
Keywords: Boundary Layer Aerodynamics; Hypersonic Aerodynamics; Heat Transfer